Wideband Lithium Niobate FBAR Filters. (18th February 2013) - Baron, Thomas; Lebrasseur, Eric; Bassignot, Florent; Wang, Haixia; Ballandras, Sylvain; Fan, Ji; Catherinot, Lise; Chatras, Matthieu; Monfraix, Philippe; Estagerie, Laetitia
Abstract : Filters based on film bulk acoustic resonators (FBARs) are widely used for mobile phone applications, but they can also address wideband aerospace requirements. These devices need high electromechanical coupling coefficients to achieve large band pass filters. The piezoelectric material LiNbO3 complies with such specifications and is compatible with standard fabrication processes. In this work, simple metal—LiNbO3 —metal structures have been developed to fabricate single FBAR elements directly connected to each other on a single chip. A fabrication process based on LiNbO3 /silicon Au-Au bonding and LiNbO3 lapping/polishing has been developed and is proposed in this paper. Electrical measurements of these FBAR filters are proposed and commented exhibiting filters with 8% of fractional bandwidth and 3.3 dB of insertion losses. Electrical measurements show possibilities to obtain 14% of fractional bandwidth. These devices have been packaged, allowing for power handling, thermal, and ferroelectric tests, corresponding to spatial conditions.